ONLINE OR OFFLINE EDUCATION. WHICH ONE IS MORE PREFERABLE? - Nazarova Nigora; Berdikulova Feruza (Western European Studies, 2024)
This article explores the comparative advantages and disadvantages of online and offline education methods, particularly in the context of the COVID-19 pandemic. Through a survey conducted among 105 graduates of UzSWLU, the study examines preferences and impacts on various aspects of student development, including time management, selfdiscipline, networking, and health
Keywords: Online education; Offline education; Hybrid education